2006
DOI: 10.1007/s00213-006-0558-1
|View full text |Cite
|
Sign up to set email alerts
|

Guanfacine produces differential effects in frontal cortex compared with striatum: assessed by phMRI BOLD contrast

Abstract: These data suggest that guanfacine can decrease neuronal activity in the caudate while increasing frontal cortex activity. This ability to change neuronal activity in specific areas of rat brain that are known to be impaired in ADHD (Solanto MV, Behav Brain Res 130:65-71, 2002) may contribute to guanfacine's beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 76 publications
5
14
0
1
Order By: Relevance
“…By simultaneous application of fMRI and electrophysiological recordings, some authors have associated negative BOLD responses with local decreases in neuronal activity (Shmuel et al 2006). These results would be in agreement with Easton and co-workers who also found widespread negative BOLD in STR and NAcc of young adult rats treated with guanfacine or atomoxetine (Easton et al 2007a;Easton et al 2006). These drugs may act on the prefrontal cortex, which in turn could exert its inhibitory control on subcortical brain regions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…By simultaneous application of fMRI and electrophysiological recordings, some authors have associated negative BOLD responses with local decreases in neuronal activity (Shmuel et al 2006). These results would be in agreement with Easton and co-workers who also found widespread negative BOLD in STR and NAcc of young adult rats treated with guanfacine or atomoxetine (Easton et al 2007a;Easton et al 2006). These drugs may act on the prefrontal cortex, which in turn could exert its inhibitory control on subcortical brain regions.…”
Section: Discussionsupporting
confidence: 84%
“…Other physiological parameters, like systemic blood pressure or haemogas composition, may specifically affect the BOLD signal and might represent a 'bias'. Such parameters were monitored in our rats and were in agreement with those found by Easton and co-workers in rats of comparable body weight (Easton et al 2006). Despite the expected age-dependent basal differences found for HR and pCO 2 , all values still remained within the physiological range (Rioja et al 2006;Sharp and LaRegina 1998).…”
Section: Discussionsupporting
confidence: 65%
“…Some authors have associated negative BOLD responses with local decreases in neuronal activity (Shmuel et al 2006). These results agree with those of Easton and coworkers who also found widespread negative BOLD in the striatum of young adult rats (Easton et al 2006(Easton et al , 2007 treated with guanfacine or atomoxetine, two alternative drugs for ADHD therapy. As with guanfacine and atomoxetine, MPH appears to have the ability to "turn down" striatal activity in the immature brain of adolescent and young adult rats, which may account for its beneficial modulatory role in the treatment of ADHD (Levy and Swanson 2001).…”
Section: Pharmacological Imaging Of Mph In the Adolescent Forebrainsupporting
confidence: 89%
“…In animals, suboptimal prefrontal NE results in a phenotype similar to ADHD, and NE agonists and antagonists enhance and reduce working memory function, respectively [reviewed in Brennan and Arnsten, 2008]. Further, pharmacological fMRI studies in rats showed reduction in striatal structures and increase in frontal cortex, relative to activation without atomoxetine [Easton et al, 2006[Easton et al, , 2007; there are no human fMRI studies with these medications. Thus, efficacy of NE agonists for ADHD is likely to be mediated by modulating prefrontal-striatal functional relationships.…”
Section: Effects Of Medicationmentioning
confidence: 97%